Contaminants' immobilisation of incinerated air pollution control residue and rubber sludge using respectively calcium aluminate cement and ordinary portland cement with rice husk ash via stabilisation/solidification technique - Abdul Latif Abdul Rani (School of Environmental Engineering, Universiti Malaysia Perlis, 2014)
The aim of this research is to immobilise heavy metals and non hazardous contaminants such as chlorides and sulphates within these wastes using stabilisation/solidification (S/S) technique. The objectives of this study were to study the effects of waste and RHA addition to compressive strength, to assess the effectiveness of RHA in immobilising the contaminants via analysing the leaching pattern and also to evaluate the stability and disintegration of the mineral phases from the stabilised/solidified sample.